MASSAGE EFFECTIVITY WITH AROMATHERAPY FRANGIPANI TO COMFORT OF THE RELATION OF SEXUAL AT MENOPAUSE MOTHER - Anantasari, Ririn; Setyowati, Setyowati; Handiyani, Hanny (Jurnal Keperawatan, 2011)
Mother facing a period of menopause will experience problems physiologically psychological and like sweating nocturnal, dryness of vagina resulting pain in bone when correlating sexual, worries and less self confidence. Sigh is not balmy when correlating deductible sexual by giving intervention of treatment appropriate causing can increase quality of life at menopause mother. Intention of this study is to know massage effectivity with aromatherapy frangipani to comfort of the relation of sexual at menopause mother. 40 responders involved in this research consisted of 20 responders at group of intervention and 20 responders at group of control. This research applies method quasi experiment of type pre and post test with group control. Result is showing existence of difference having a meaning balmy taste when correlating sexual at group of intervention at before and after intervention (p < 0,0005). From result of research is recommended by massage with aromatherapy frangipani to health officer in public and clinic climaterium as part of treatment upbringing as a mean to increases comfort of the relation of sexual at menopause mother.